PALATE SENSOR, TONGUE MOVEMENT MONITORING SYSTEM AND TONGUE MOVEMENT MONITORING METHOD - OTANI MARIKO; NISHI ERI; OKADA JUN (2024)
To provide a palate sensor having excellent speech stability.SOLUTION: A palate sensor for measuring tongue movements when coming into contact with a palate of a subject, the palate sensor comprises: a flexible base plate including a mounting surface to be mounted on a hard palate of a subject, and a pressure surface to be pressed by a tongue of the subject; a plurality of pressure sensors provided on the pressure surface of the flexible base plate; and a plurality of stretchable wires provided on the flexible base plate and respectively, electrically connected to the plurality of pressure sensors.SELECTED DRAWING: Figure 1 【課題】発話安定性に優れた口蓋センサを提供する。【解決手段】本発明の口蓋センサは、被験者における口蓋接触時の舌運動を測定する、口蓋センサであって、被験者の硬口蓋に装着される装着面と被験者の舌により押圧される押圧面とを有する、柔軟性基板と、柔軟性基板の押圧面に設けられた、複数の圧力センサと、柔軟性基板に設けられており、複数の圧力センサのそれぞれに電気的に接続した、複数の伸縮性配線と、を備えるものである。【選択図】図１